1998
DOI: 10.1136/jnnp.65.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dendritic spine density on cerebral cortical pyramidal neurons in schizophrenia

Abstract: Objective-A pilot study of the density of dendritic spines on pyramidal neurons in layer III of human temporal and frontal cerebral neocortex in schizophrenia. Methods-Postmortem material from a group of eight prospectively diagnosed schizophrenic patients, five archive schizophrenic patients, 11 nonschizophrenic controls, and one patient with schizophrenia-like psychosis, thought to be due to substance misuse, was impregnated with a rapid Golgi method. Spines were counted on the dendrites of pyramidal neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
383
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(432 citation statements)
references
References 33 publications
33
383
0
9
Order By: Relevance
“…In fact, a recent study has demonstrated a strong correlation between the loss of asymmetric spine synapses in monkey PFC and cognitive impairment during aging (Peters et al, 2008). Several groups have reported dystrophic changes in frontal cortical pyramidal cell dendrites in schizophrenia, including decreases in dendritic length, branching, and spine density (Black et al, 2004;Broadbelt et al, 2002;Garey et al, 1998;Glantz and Lewis, 2000;Kalus et al, 2000;Kolluri et al, 2005), consistent with the hypothesis that these changes are involved in the cognitive dysfunction that typifies the disorder. It is not currently known though whether the pathological changes in the cortex in schizophrenia are fixed or can be altered by treatment with antipsychotic drugs.…”
Section: Introductionmentioning
confidence: 48%
“…In fact, a recent study has demonstrated a strong correlation between the loss of asymmetric spine synapses in monkey PFC and cognitive impairment during aging (Peters et al, 2008). Several groups have reported dystrophic changes in frontal cortical pyramidal cell dendrites in schizophrenia, including decreases in dendritic length, branching, and spine density (Black et al, 2004;Broadbelt et al, 2002;Garey et al, 1998;Glantz and Lewis, 2000;Kalus et al, 2000;Kolluri et al, 2005), consistent with the hypothesis that these changes are involved in the cognitive dysfunction that typifies the disorder. It is not currently known though whether the pathological changes in the cortex in schizophrenia are fixed or can be altered by treatment with antipsychotic drugs.…”
Section: Introductionmentioning
confidence: 48%
“…A link between abnormal neural spines and mental retardation was suggested for first time by (Purpura 1974). Also, mental disorders such as schizophrenia is associated with decreased density of dendritic spines in neocortical pyramidal neurons (Garey et al, 1998). In addition, patients with Down syndrome have a decreased spine density in neocortex (Takashima et al, 1989) and hippocampus (Ferrer and Gullotta 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models in which GSH levels are decreased show hypofunction of NMDA receptors (Steullet et al, 2006). During development, the transitory decrease of GSH levels in conjunction with an increase in dopamine result in morphological (Cabungcal et al, 2006;Gheorghita et al, 2007, unpublished work) and behavioral (Cabungcal et al, 2007;Castagné et al, 2004a, b) impairments in animals that are similar to those observed in schizophrenia (Garey et al, 1998;Glantz and Lewis, 2000;Kolluri et al, 2005;Robbins, 2005). Several studies have demonstrated that the administration of NMDA receptor antagonists, such as phencyclidine or ketamine, induces in control subjects symptoms that are similar to those observed in schizophrenia and exacerbates these symptoms in patients (Krystal et al, 1994).…”
Section: Introductionmentioning
confidence: 95%